Effectiveness of three biomimetic remineralization procedures in artificial caries-affected dentin - an in-vitro pilot study - Costa,Rosário (2024)
Abstract Objectives: Biomimetic remineralization strategies offer promising paths for managing caries- affected dentin by restoring its morphology and structural integrity. This pilot study aimed to assess the morphological and structural changes in dentin following two chemical artificial caries-affected dentin (ACAD) protocols, evaluate the effects of three biomimetic remineralization procedures (BRPs) on dentin structure, and determine the most effective ACAD-BRP combination. The BRPs studied were casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), self-assembling P11-4 (SAP-P11-4), and calcium phosphate polymer-induced liquid precursor (Ca/P-PILP). Methods: Seventy-two specimens of healthy human dentin were divided into twelve groups. Half of each group’s samples were analyzed using field-emission gun environmental scanning electron microscope/energy dispersive X-ray, while the other half were analyzed by X-ray diffraction and micro-Raman spectroscopy. Results: Results demonstrate alterations in dentin morphology and structure induced by the ACAD protocols, affirming their effectiveness in mimicking caries-affected dentin. Among the BRPs evaluated, CPP-ACP emerged as the most promising agent for promoting remineralization and restoring dentin structure. The combination of pH cycling with CPP-ACP exhibited superior efficacy in promoting dentin remineralization compared to other combinations. Conclusions: These findings highlight the potential of biomimetic remineralization strategies, particularly CPP-ACP combined with pH cycling, as effective approaches for managing caries-affected dentin and preserving dental health.